Royalties minerais e capacidade de gestão em governos locais: um estudo em municípios mineradores de Minas Gerais - Ferreira, Thamiris Rodrigues (2013)
The present study aims to diagnose the management of local public capacity of Minas Gerais municipalities mining dependent, to evaluate their qualification level, identify limitations to institutional strengthening of management and investigate how municipal management has evolved from the receipt of funds from the “Compensação Financeira pela Exploração de Recursos Minerais” (CFEM). The 'management capacity' variable was operationalized based on the 'Government Performance Project' (GPP) methodology, which proposes five dimensions of analysis: financial management, capital management, human resources management, information technology management and managing for results. The study seeks to answer the following questions: do Minas Gerais towns economically dependent of mineral extraction activity demonstrate municipal management capacity in performing their function? The extra resources receipt has allowed improving the quality of municipal management? For this, we developed a multiple cases study in three Minas Gerais towns which are dependent of the mineral extraction activity for many years: Mariana, Catas Altas and São Gonçalo do Rio Abaixo. Semi-structured interviews were conducted with technicians, municipal secretaries, mayors and citizens in order to investigate the management capacity of local government in these cities. Although the three towns have presented common characteristics, such as dependence of mineral activity, territorial proximity, economic environment and high levels of tax revenue, it is noted that these cities represent three different realities, with distinct levels of development. It was identified that the studied municipalities, especially Catas Altas and São Gonçalo do Rio Abaixo adopt best practices in municipal management. Mariana has recently made good initiatives in managing change, however, political changes have prevented these implementations. Besides the dimensions of GPP analysis, we could identify other relevant factors to the institutional strengthening of management such as planning, manager profile and political context. It was also found that the impacts of mining are not restricted to the mining town, but also to cities located around the mine.